Designing Educational Webtoons as a Medium for Education and Character Building in Adolescence - Mufidah, Difa Dhiya; Pandanwangi, Brilindra (Fakultas Bahasa dan Seni UNP, 2024)
This research aims to design educational webtoons as a medium for character education targeted at adolescents, employing a design process that includes pre-production, production, and post-production stages (Owens, 2020). Utilizing a quantitative approach, closed questionnaires were distributed to webtoon readers via Google Forms, revealing that the use of webtoons for character education is effective and well-received. The values conveyed include tolerance, friendliness, discipline, hard work, independence, religiosity, honesty, creativity, curiosity, and love of reading. However, improvements are needed in areas such as panel spacing, character depth, and the relevance of presented issues to teenagers. The theoretical framework is based on character education principles that emphasize the development of ethical reasoning and behavior among students; this study supports the idea that engaging storytelling through webtoons can effectively promote essential virtues among youth, enhancing their moral development and social-emotional competencies.